2014
DOI: 10.1177/1045389x14546651
|View full text |Cite
|
Sign up to set email alerts
|

Material strength consideration in the design optimization of nonlinear energy harvester

Abstract: Cantilever-based piezoelectric energy harvesting from ambient vibrations is a viable solution for powering wireless sensors and low-power electronic devices. For realization of such technology, it is imperative to design the energy harvester with higher power output and wider operating bandwidth. The main practical constraints on the design of harvester are system mass, volume, and strength of the material. In pursuit of better performance, material strength has yet been considered in designing nonlinear energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…In this case, it is assumed that the magnetic dipoles' directions and the transverse deflection of the system are always vertically aligned. It was demonstrated by Upadrasta et al [45] that this model is accurate only when the spacing distance between the two magnets is sufficiently large. They showed that the dipole model gives erroneous predictions for the magnetic force when the spacing distance between the two magnets is smaller than 6.5 mm.…”
Section: Magnetic Force Representationmentioning
confidence: 96%
See 3 more Smart Citations
“…In this case, it is assumed that the magnetic dipoles' directions and the transverse deflection of the system are always vertically aligned. It was demonstrated by Upadrasta et al [45] that this model is accurate only when the spacing distance between the two magnets is sufficiently large. They showed that the dipole model gives erroneous predictions for the magnetic force when the spacing distance between the two magnets is smaller than 6.5 mm.…”
Section: Magnetic Force Representationmentioning
confidence: 96%
“…Consequently, the expression of the magnetic force depends on the number of considered mesh elements and hence a higher number of mesh elements is needed to have an accurate representation which can significantly increase the computational time. More details about this methodology can be found in [45]. Upadrasta et al [45] reported that a discretization error in the order of 0.001 N is obtained when considering a mesh resolution of 25 elements in the radial direction and 25 elements in the circumferential direction.…”
Section: Magnetic Force Representationmentioning
confidence: 98%
See 2 more Smart Citations
“…Shafer et al (2012) explored the limiting conditions for the utilization of a harvester beam from the ultimate strength considerations of the constituent materials. Upadrashta et al (2014) examined the material strength considerations and suggested that a limiting strain of 1000 渭蔚 for the MFC transducer would restrict it within the linear range. Though these studies have provided useful guidelines, it is unlikely that the field conditions would be uniform and any harvester designed based on such conditions would lead to a very conservative design.…”
Section: Analytical Modelingmentioning
confidence: 99%